Dampak Implementasi PSAK 72/115 Terhadap Relevansi Nilai Informasi Akuntansi pada Sub-Sektor Telekomunikasi, Konstruksi, Properti & Real Estate di BEI 2020-2024 - Dwi Nadya Puspita; Retno Yuni Nur Susilowati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the impact of PSAK 72/115 implementation on the value relevance of accounting information in telecommunications, construction, and property and real estate subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The implementation of PSAK 72/115, which adopts IFRS 15, changes the revenue recognition mechanism based on the fulfillment of performance obligations, thus potentially affecting the relevance of accounting information for investors. This study uses a quantitative approach with secondary data obtained from annual financial reports and company stock price data. The research sample was selected using a purposive sampling method and resulted in 77 companies with a total of 307 observation data after the outlier process. Data analysis was carried out using multiple linear regression with the Ohlson Price Model approach to measure the value relevance of accounting information through Earnings per Share (EPS) and Book Value per Share (BVPS). The results of this study indicate that the implementation of PSAK 72/115 weakens the value relevance of earnings, as measured by Earnings per Share (EPS), but strengthens the relevance of book value, as measured by Book Value per Share (BVPS). Furthermore, the impact of PSAK 72/115 implementation varies across the study subsectors. In the property and real estate subsector, PSAK implementation has no significant effect on value relevance, but it does strengthen the effect of BVPS on value relevance. In the construction and telecommunications subsectors, PSAK implementation significantly impacts firm value relevance. This study indicates that the implementation of PSAK 72/115 has not fully improved the value relevance of accounting information because, in the initial stages of its implementation, earnings information tends to be less stable in reflecting a company's economic value, while book value information becomes more relevant for investors in assessing companies in the capital market.